2021
DOI: 10.3390/biology10050413
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Long-Term Continuous Light Exposure and Western Diet on Adropin Expression, Lipid Metabolism, and Energy Homeostasis in Rats

Abstract: Long-term continuous light exposure (CL) and western diet (WD) effects on Adropin expression, RORα, and Rev-erb-α nuclear receptors and energy homeostasis were studied in rats. Thirty-two male Wistar rats (250–290 g) were enrolled for 3 months in the following groups (n = 8/group): (a) Normal control group (NC), (b) CL group, (c) WD group, and (d) CL + WD group. Then, indirect calorimetry and food intake (FI) were measured. Finally, Adropin, hormone-sensitive lipase (HSL), adipocyte triglyceride lipase (ATGL),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Similarly, a study by Abulmeaty et al, [12] investigated the impact of prolonged continuous exposure on energy homeostasis as well as adropin expression, RORα, and Rev-erb-α nuclear receptors in 32 rats over a period of 3 months. Continuous light exposure was found to raise total energy expenditure.…”
Section: Effect Of Photic Stress On Autonomic Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study by Abulmeaty et al, [12] investigated the impact of prolonged continuous exposure on energy homeostasis as well as adropin expression, RORα, and Rev-erb-α nuclear receptors in 32 rats over a period of 3 months. Continuous light exposure was found to raise total energy expenditure.…”
Section: Effect Of Photic Stress On Autonomic Nervous Systemmentioning
confidence: 99%
“…Stenvers et al, [17] reported a novel means of creating circadian desynchronization in rats. In their study, they exposed rats to 12 Ishida et al, [18] showed that exposure to light orchestrated the expression of the adrenal gland gene and the underlying mechanism involved suprachiasmatic nucleussympathetic nervous system connection. One of the most extensively documented suprachiasmatic nucleus-sympathetic nervous system connections is the retinohypothalamic-pineal gland pathway, through which ambient light passes through intrinsically photosensitive mesopic retinal ganglionic cells to the suprachiasmatic nucleus of the anterior hypothalamus and from there to the pineal gland via superior cervical ganglion.…”
Section: Effect Of Photic Stress On Autonomic Nervous Systemmentioning
confidence: 99%